2020
DOI: 10.1080/26395916.2020.1833986
|View full text |Cite
|
Sign up to set email alerts
|

Including stakeholders’ perspectives on ecosystem services in multifunctionality assessments

Abstract: Multifunctional landscapes are used and shaped by a range of different stakeholders. The high number of diverging values, interests or demands in such landscapes can lead to conflicts that impact sustainability goals. In this study, our aim was to include stakeholders' valuations of ecosystem services in multifunctionality assessments and thereby to identify different and possibly contradictory perspectives on landscape multifunctionality. Two European cultural landscapes, the Vereinigte Mulde (Germany) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 54 publications
1
19
0
Order By: Relevance
“…The COVID-19 pandemic has also introduced more concerns regarding pets, such as (1) how to care for pets during such crises in the future, (2) whether there are zoonotic concerns associated with caring for a pet, and 3) what repercussions there are for pet care [69,76]. Thus, urban planning is challenged with addressing these and other demands of pet owners, while balancing them with those of other interest groups, for instance through the cooperation between multiple beneficiaries and the identification of stakeholder-specific multifunctionality hotspots [77].…”
Section: Implications For Urban Planningmentioning
confidence: 99%
“…The COVID-19 pandemic has also introduced more concerns regarding pets, such as (1) how to care for pets during such crises in the future, (2) whether there are zoonotic concerns associated with caring for a pet, and 3) what repercussions there are for pet care [69,76]. Thus, urban planning is challenged with addressing these and other demands of pet owners, while balancing them with those of other interest groups, for instance through the cooperation between multiple beneficiaries and the identification of stakeholder-specific multifunctionality hotspots [77].…”
Section: Implications For Urban Planningmentioning
confidence: 99%
“…These visual indicators are developed as part of landscape characters (LCs), to improve the understanding of the relationship between people and place and make informed planning decisions (Butler, 2016;Bartlett et al, 2017). Except from the aesthetic characters, multifunctional characters are also assessed based on the potential supply of ecosystem services (Hölting et al, 2020), which includes but is not constrained to recreation, production, habitat and tourism (Howley, 2011;Gulickx et al, 2013). However, aesthetic and multifunctional characters are always studied separately because aesthetic characters are considered intrinsic values of a landscape (Jorgensen, 2011), while multifunctional characters are assessed based on the human needs (Gulickx et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, residents should be one of the primary decision makers in their communities because they share common responsibilities for the area they live (Lee, 2020). Hence, an increasing number of researchers have expressed the need to incorporate public perceptions into landscape management processes (Tress and Tress, 2003;Vouligny et al, 2009;Kristensen and Primdahl, 2019;Hölting et al, 2020), especially those residents who experience certain landscapes in their daily lives. Vouligny et al (2009) found that the inhabitants value ordinary landscapes on a set of criteria related to emotion and eveyday experience, and the visual criteria used by the experts were not important to the inhabitants.…”
Section: Introductionmentioning
confidence: 99%
“…Consideration of landscapes as multifunctional acknowledges complexity and diversity in land uses including: private recreation, residential development, energy development, and production of food, fiber, and fuel. Recent research on multifunctional landscapes has shown they support SESs via the conservation of biodiversity and supply of ecosystem services [16]. For example, Walston et al [6] showed that spatial planning for both native vegetation and solar energy facilities enhanced multiple supporting and regulating ecosystem services including pollination and sediment retention.…”
mentioning
confidence: 99%